Mudanças urbanas e afetos: estudo de uma cidade planejada - Bertini, Fátima Maria Araújo (2014)
This thesis is to study the socio-affective dimension focus of the city of New Jaguaribara - CE, northeastern Brazil, in the urban removal that was submitted, with the subtext political analysis. This city was made to give place to the inhabitants of Jaguaribara, noises from Castanhão dam in the state of Ceará. The study is understanding that urban removal which implies the compulsory transfer of the inhabitants of one city to another, or from one territory to another, interfere directly in political action and the common sentiment of the residents in the new urban space. We analyze the affects to understand the social and psychosocial changes, since they are the singularity of the social and cross the memory, ideas, action and thought. The theoretical perspectives of the Thesis are in two areas of knowledge that are social psychology and philosophy. The first, adopted the Socio-Historical Psychology. The second, to Spinoza's philosophy. The choice of Espinosa for studies of affect, led us to study the affects of the city from the perspective of policy. In ethnographic insertion, this research used three procedures to meet the affections: the field diary, narratives about the city and the Affective Maps. The socio-affective-urban narrative was constructed from in-depth interviews. These interviews also served to draw up the 'network of passive affections'. Affections were analyzed Fear, Hope, Courage fluctuation (Joy and Sorrow), the Missing and the Desire to remained. Subsequently, there is the proposal of some conceptual formulations as Uniformity blank, the Common Abstract, the Useful Resistance and Body Equal empty - Body Similar Useful